Analisis Implementasi Projek Penguatan Profil Pelajar Pancasila Kearifan Lokal Permainan Tradisional Kelas IV SD - Aminatur Rodiyah; Nur Ngazizah; Suyoto Suyoto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to present the results of the analysis of the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) for class IV elementary school as evaluation material for the creation of an even better program. This research adopts a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The data analysis stage includes data reduction, data presentation, and verification. The research results show that the school has implemented P5 in class IV based on local wisdom of traditional games, which is an ancestral heritage that must be protected and preserved. Research findings at the stages in designing P5 include the preparation stage including forming a team of facilitators but they don't yet have a decree, there is only a coordinator, then identifying school readiness, determining dimensions, themes and time allocation, preparing strategies and project modules, but teachers sometimes haven't prepared project modules. , and develop a strategy for reporting project results. Then the implementation stage includes introduction, contextualization and P5 action. The evaluation stage includes reporting results, evaluating implementation achievements and program sustainability. It can be concluded that the implementation of P5 local wisdom of traditional games is carried out in the developing stage, integrating local wisdom, and involving parents and the community as P5 partners in order to develop students' character in accordance with the noble values ​​of Pancasila.